Analisis Ambang Batas Escherichia coli Sebagai Indikator Pencemaran Pada Daging Sapi di Rumah Pemotongan Hewan Kota Jambi - Budiono, Hendra (Biospecies, 2012)
Beef is one of the Indonesian favorite foods and provides protein needed for human body’s health and growth. Rumah Pemotongan Hewan (RPH) Jambi is a slaughtering house that provides and distributes beef to traditional markets throughout Jambi City. Therefore, it is very essential to assure safetyof every piece of beef produced by the RPH. This research was undertaken in Biology UP-MIPA Laboratory, University of Jambi, from December 2009 to January 2010. The beef samples were collected from the Jambi RPH. This research employs the Most Probable Number (MPN) method, by observing the growth of Escherichia coli on Endo Agar media, starting from presumptive test until confirmative test. The experiment used 5-5-5 series reaction tubes, including the Durham fermentation tube. The results show that beef produced by the JAMBI RPH is 100% safe to be consumed. The number of Escherichia coli in the fresh beef is still below the maximum threshold level, which is 5 X 101MPN/100 ml